IMPROVING SCIENCE LEARNING OUTCOMES OF CLASS V STUDENTS AT SDN PUCANGAN III THROUGH EXPERIMENTAL METHODS - HIdayatur Rohmah; Agung Setyawan (Citra Dharma Cindekia, 2022)
Science learning should be carried out using a method that is in accordance with its nature as a product, process, and scientific attitude. One method that can be applied is the experimental method. The purpose of this study was to determine the improvement of science learning outcomes in fifth grade students of SDN Pucangan III through the experimental method. In this study, the data collection methods used were interviews, observation, tests, and documentation with quantitative qualitative data analysis techniques. The result of this research is that there is an increase in the science learning outcomes of the fifth grade students of SDN Pucangan III in each cycle. At the pre-cycle stage, the percentage of the number of students who completed was only 60% with an average value of 67. In the first cycle there was no increase in the number of students who completed, which was still in the range of 60%, but there was a slight increase in the average learning outcomes to 68%. In cycle II, the percentage of the number of students completed and student learning outcomes both increased, respectively to 80% and 78. Based on this, it can be concluded that the experimental method can improve the learning outcomes of fifth grade students at SDN Pucangan III in science learning.